Penarapan E-Learning Berbantuan Canva Untuk Meningkatkan Hasil Belajar Siswa - Oky Dwi Noor Jannah; Wawan Shokib Rondli (Lembaga Pendidikan Hikmatun Najah (LPHN) Blora, 2023)
The purpose of this study was to determine the increase in learning outcomes and student learning activities in the application of e-learning to improve learning outcomes in students of class VI SD 2 Jepang. This research was contucted at SD 2 Jepang, Mejobo, Kudus in class VI with a total of 29 students. This study used classroom action research consisting of 2 cycles. Each cycle consists of 2 meetings. Data collection techniques used are test and observation sheets. Data analusis techniques using quantitative data analysis and qualitatitve data analysis. The result showed that the student learning outcomes in pre-cycle showed the number 70 then became 74 in cycle I and became 86 in cycle II. While student learning activities in the pre-cycle show a number of 70 rising to 73 in cycle I and to 74 in cycle II